Integrative metabolic analysis of orbital adipose/connective tissue in patients with thyroid-associated ophthalmopathy - Huang, Jiancheng; Chen, Meng; Liang, Yu; Hu, Yuxiang; Xia, Weiyi; Zhang, Yihan; Zhao, Chen; Wu, Lianqun (Frontiers in Endocrinology, 2022)
Objective: Thyroid-associated ophthalmopathy (TAO) is a disfiguring autoimmune disease, which destroys the structure of orbital tissues and even threatens vision. Metabolic reprograming is critical in autoimmune diseases; however, the metabolic basis of TAO remains to be clarified. Our study aimed to reveal the metabolic profile of TAO. Methods: Orbital adipose/connective tissues from eleven TAO patients and twelve control subjects were collected during surgeries and analyzed with liquid chromatograph-mass spectrometer. Orthogonal partial least-squares discrimination analysis (OPLS-DA), variable importance in projection (VIP), heat map, and volcano plot were used to reveal metabolic profile in TAO. Pathway analysis and metabolites-gene analysis were utilized to explore potential metabolic metabolism in TAO. Results: 3038 metabolites were detected in samples from the TAO patients and the controls. OPLS-DA analysis of the metabolomics results showed two distinguished groups, demonstrating that TAO has a unique metabolome. Univariate tests identified 593 dysregulated metabolites (P < 0.05), including 367 increased metabolites and 226 decreased metabolites. Pathway analysis showed that changed metabolites were enriched in cholesterol metabolism, choline metabolism in cancer, fat digestion and absorption, regulation of lipolysis in adipocytes, and insulin resistance. In addition, metabolites-gene analysis illustrated that cholesterol metabolism was involved in the pathogenesis of TAO. Endoplasmic reticulum stress-related genes (ATF6, PERK, and IRE1α) expressions were higher in TAO orbital tissues than in control orbital tissues verified by western blot. Additionally, the expression level of diacylglycerol acyltransferase 1 (DGAT1), a key metabolic protein for triacylglycerol synthesis, was increased in orbital tissues of TAO detected by qRT-PCR, indicating disrupted cholesterol metabolism in TAO. Conclusion: The present study demonstrated different metabolite profiles and potential metabolic mechanisms in TAO.